"On Chorea": 150 Years of the Beginning of Hope. Issue 11 (10th June 2022) - Franklin, Gustavo L.; Teive, Hélio A.G.; Meira, Alex T.; Nepomuceno, Adriana M.T.; Tabrizi, Sarah J.
Abstract: "On Chorea" by George Huntington was published on April 13, 1872, in The Medical and Surgical Reporter of Philadelphia . Despite being a milestone in the recognition of the disease that later would bear his name, some myths and curiosities continue to surround the history of this publication and its author. In this History, the authors pay tribute to the 150th anniversary of the publication of this iconic article. © 2022 International Parkinson and Movement Disorder Society.